2021
DOI: 10.3389/fendo.2020.589340
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Features of a Large Monocentric Series of Familial Non-Medullary Thyroid Cancers

Abstract: Several low penetration susceptibility risk loci or genes have been proposed in recent years with a possible causative role for familial non-medullary thyroid cancer (FNMTC), though the results are still not conclusive or reliable. Among all the candidates, here fully reviewed, a new extremely rare germline variant c.3607A>G (p.Y1203H) of the DUOX2 gene, has been recently reported to co-segregate with the affected members of one non-syndromic FNMTC family. We aimed to validate this finding in our series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The trend toward more favorable primary MTC stages leads to the need to avoid overtreatment by adapting the resection strategy on a case-by-case basis. Prerequisites for this are the comprehensive clinical and laboratory diagnosis of the individual case as well as the structural availability of qualified pathologists, in order to obtain an intraoperative frozen section analysis though considering the above reported limitations (32)(33)(34)(35). If the preoperative criteria indicate a sporadic, unifocal, and with expected biochemical cured MTC, and the intraoperative frozen section excludes desmoplasia and capsular infiltration or finds them only to a minor extent, the resection could be limited.…”
Section: Limited Forms Of Resection For Intrathyroidal Mtcmentioning
confidence: 99%
“…The trend toward more favorable primary MTC stages leads to the need to avoid overtreatment by adapting the resection strategy on a case-by-case basis. Prerequisites for this are the comprehensive clinical and laboratory diagnosis of the individual case as well as the structural availability of qualified pathologists, in order to obtain an intraoperative frozen section analysis though considering the above reported limitations (32)(33)(34)(35). If the preoperative criteria indicate a sporadic, unifocal, and with expected biochemical cured MTC, and the intraoperative frozen section excludes desmoplasia and capsular infiltration or finds them only to a minor extent, the resection could be limited.…”
Section: Limited Forms Of Resection For Intrathyroidal Mtcmentioning
confidence: 99%
“…As first step, we mined the literature for candidate non-syndromic FNMTC susceptibility genes. In total, we identified 114 candidate genes across 32 independent studies ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ). A list of included genes and studies is provided in Supplementary data (Supplementary Table 1, see section on supplementary materials given at the end of this article).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of different kindreds with FNMTC advocates for an autosomal dominant inheritance with incomplete penetrance and variable expressivity ( 1 , 4 , 5 , 6 , 7 , 8 ). In the past years, several studies reported FNMTC-associated chromosomal loci ( 3 , 15 , 16 , 17 , 18 ) and predisposing risk variants in over 100 genes, including SRGAP1 , CHEK2 , SRRM2 , TIFF-1/NKX2 , FOXE1 , NOP53 , HABP2 , ANO7 , CAV2 , KANK1 , PIK3CB , PKD1L1 , PTPRF , BROX , RHBDD2 , ATM , MAP2K5 , EWSR1 , POT1 , TIAM1 and SPRY4 ( 1 , 3 , 7 , 12 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ). Recently, using whole-genomic sequencing, a group has identified variants in genes that were enriched in tumourigenic signalling pathways such as MAPK/ERK and PI3K/AKT in families with NMTC ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this same family, in addition to the germinal missense variant p.Tyr1203His (c.3607A>G) in DUOX2, the p.Gln61Arg somatic mutation in KRAS was detected in a follicular variant of mPTC and the somatic mutation of BRAF V600E in a classic form of mPTC ( 26 ). Unfortunately, the role of this germline variant could not be confirmed in a recent series of 33 unrelated Italian FNMTC kindreds ( 91 ).…”
Section: Susceptibility Genes Associated With Ns-fnmtcmentioning
confidence: 97%